Covid, Brexit and the Anglosphere : frameworks for future trade and economic growth - Simmons, Richard, 1957-; Culkin, Nigel (Emerald Publishing Limited, 2022)
What is the role of trade to both expedite growth and to provide the transformative innovations needed in our post-Pandemic, post-Brexit, unstable world? Using historical examples to demonstrate how complex forces interplay into virtuous or vicious cycles of cumulative causation, Simmons and Culkin suggest alternative trade approaches to drive economic growth. Set within the socio-political space defined by a nascent Anglosphere and its implicit nationalism, they map alternative frameworks to embolden entrepreneurs to make the future. With fresh thinking Covid, Brexit and The Anglosphere equips academics, students, policymakers and general readers with the tools to drive growth in a post-Pandemic post- Brexit fragmenting world order facing rapidly advancing technical change.